Pengembangan Media Animasi Berbasis Adobe CC Dalam Pembelajaran Berbasis Masalah Pada Materi Fluida Dinamis - Lalu Gilang Istiqlal; Sutrio Sutrio; Nina Nisrina (Jurnal Ilmiah Profesi Pendidikan, 2025)
The purpose of this research is to determine the validity of Adobe CC based animation media in problem-based learning for improving students’ critical thinking skills on dynamic fluid material. This research employed a research and development (R&D) design by Thiagarajan with 4d model (define, design, develop, and disseminate). The findings revealed that Adobe CC-based animation media in problem-based learning obtained an average Aiken’s V score of 0.90 and reliable validation results from all experts. The Adobe CC-based animation media in problem-based learning are highly valid for enhancing students’ critical thinking skills on dynamic fluid topics.